Power Dispatching of Transportable Energy Storage System for Post-disaster Restoration Scheme of Port: The AES-Based Joint Restoration Scheme - Xia, Wenjia; Shan, Qihe; Teng, Fei; Li, Tieshan (Frontiers in Energy Research, 2021)
In recent years, the rapid development of artificial intelligence, Big Data, Cloud Computing, etc., rapidly develops, synergy development of the transportation-energy-information based triple play has been accelerated. The all-electric ship (AES) is satisfied with the demand for both the unreasonable resource configuration of port energy system and low energy efficiency caused by sudden disasters. As a power carrier unit, AES has great potential in improving the resistance of port power distribution network for large-area blackout. Therefore, in this paper, a joint post-disaster restoration scheme for AESs and distribution generation scheduling in ports’ microgrid (MG) is proposed to minimize the cost of post-disaster restoration including customer interruption cost and AES operation cost. The time-space network (TSN) model which describes the scheduling of AESs is applied to compare the grid resilience and flexibility of AES-based joint dispatching and only relying on distributed generation equipment in post-disaster restoration. The joint scheduling problem is formulated as a mixed-integer linear programming. The proposed model and scheme are tested in a system with 3 ports and 4 AESs verified the resilience of the port power distribution network with AESs.